Text, context and construction of identity - Kumar, Rejesh; Prakash, Om (Cambridge Scholars Publishing, 2019)
Language is central to our existence and it happens to be the most sophisticated product of the human mind. It is inconceivable to think of ourselves, our societies, our ideas, cultures or identities without language. It is the primary means of socialization, and whatever we know is a result of it. It is the primary medium of construction and dissemination of knowledge, and structures our thought processes in important ways that constitute our identity. In very complex ways, it interacts with the social, political and economic power structures that remain significant in defining the identities.